Whats drive someone to share their knowledge? Indonesia virtual community case - Satria, Deki (Information Systems - Universitas Pesantren Tinggi Darul Ulum, 2021)
A virtual community is one form of Community of Practices that resides on the internet. This community consists of people who share problems or interests in specific topics. A lot of knowledge comes from this kind of community where the members shared their knowledge voluntarily. Knowledge itself is a valuable resource that gives the owner have an advantage. This research tried to observe what are the driver of this behavior. Knowing these variables could help the organization in defining knowledge sharing system functionality. The variables collected using PRISMA Systematic Literature Review (SLR) protocols, and the hypotheses tested using Partial Least Squares Structural Equation Modeling (PLS-SEM). From this research, we observed that self-efficacy and supporting others significantly influence someone to share their knowledge.